Mengembangkan Motorik Kasar Anak Melalui Bermain Papan Titian Usia 5-6 Tahun Di PAUD Tunas Harapan Desa Bakit - Lestari, Devi Rena (ICEJ : Islamic Childhood Education Journal, 2022)
Motor development determines the child's skills in moving. Basically, children like to play, to hone motor skills can be done by playing the boardwalk. This study aims to determine the development and results of gross motor development of children aged 5-6 years through playing the catwalk in PAUD Tunas Harapan, Bakit Village.The method used in this research is descriptive qualitative, by interviewing principals, teachers at PAUD Tunas Harapan, Bakit Village, plus data and documentation relevant to this research.The results of this study indicate that the gross motoric development of children aged 5-6 years through playing boardwalk at PAUD Tunas Harapan Bakit Village which can be assessed from the aspect of locomotor motion is good, non-locomotor motion is not good, manipulative results are not so good. So, overall it can be said that the implementation has not been so good. Meanwhile, the results of children's gross motor development can be seen in aspects of walking without holding on and fast, walking without holding on but slowly, and walking requires grip to feel afraid. Overall, the results are pretty good, although there are still people who are afraid of heights. For this reason, it is expected that teachers at PAUD Tunas Harapan Desa Bakit are required to be more innovative, creative, and provide motivation, give examples before carrying out activities, be carried out repeatedly and supervise closely so that the results can be maximized.